2016
DOI: 10.1123/ijsnem.2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Vitamin D Status Negatively Affects Muscular Strength and Power of Collegiate Athletes

Abstract: Increasing evidence indicates that compromised vitamin D status, as indicated by serum 25-hydroxyvitamin D (25-OH D), is associated with decreased muscle function. The purpose of this study was to determine the vitamin D status of collegiate athletes residing in the southern U.S. and its effects on muscular strength and anaerobic power. Collegiate athletes (n = 103) from three separate NCAA athletic programs were recruited for the study. Anthropometrics, vitamin D and calcium intake, and sun exposure data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The high prevalence of low levels of vitamin D was also found in the studies on Swedish young soccer players and Canadian young hockey players residing in regions with low levels of solar insolation [34,35]. However, prolonged insolation is not a guarantee of sufficient formation of vitamin D and its deficiency is also widespread among athletes permanently residing in the southern regions [36]. Reduced workload in comparison to summer and autumn may provide a possible explanation of lower prevalence of vitamin D deficiency among young Russian soccer players during winter season.…”
Section: Discussionmentioning
confidence: 88%
“…The high prevalence of low levels of vitamin D was also found in the studies on Swedish young soccer players and Canadian young hockey players residing in regions with low levels of solar insolation [34,35]. However, prolonged insolation is not a guarantee of sufficient formation of vitamin D and its deficiency is also widespread among athletes permanently residing in the southern regions [36]. Reduced workload in comparison to summer and autumn may provide a possible explanation of lower prevalence of vitamin D deficiency among young Russian soccer players during winter season.…”
Section: Discussionmentioning
confidence: 88%
“…Vitamin D insufficiency affects exercise performance and injury prevention; thus, it is an essential topic of interest for athletes. Moreover, it is also known to impact athletic performance; however, most previous studies have assessed jumping and running performances [26]. Thus, our study is the first study to analyze the association between vitamin D levels and shoulder rotator cuff strength, which is involved in one of the most forceful movements in volleyball, i.e., spiking.…”
Section: Discussionmentioning
confidence: 98%
“…This data therefore suggests, that submariners are at increased risk for muscle mass loss. The causes of the accelerated reduction in fat-free mass remain speculative, but may relate to the irregular daily rhythm induced by shift-work [25,26], voided sunlight/vitamin D deficiency [27,28], chronic stress [10], and altered dietary pattern, e.g., low protein [29], low eating frequency [30,31]. Notably, in other studies on submariners, a reduction in fat-free mass was not observed [7,32], and vitamin D supplementation did not increase fat-free mass during 3-month submarine deployment [6].…”
Section: Discussionmentioning
confidence: 99%